Synthesis of 3-(2-furylmethylene)-2,4-pentanedione using DL-Alanine functionalized MCM-41 catalyst via Knoevenagel condensation reaction - Appaturi, Jimmy Nelson; Selvaraj, Manickam; Hamid, Sharifah Bee Abd (Elsevier, 2018)
To use as the efficient solid base catalysts, alanine functionalized MCM-41 (Alanine-MCM-41), catalysts viz. 16Alanine-MCM-41 and 8Alanine-MCM-41, were successfully prepared by post-grafting method using MCM-41 synthesized by basic sol-gel method. The synthesized Alanine-MCM-41 catalysts were characterized by several instrumental techniques such as XRD, N2-sorptions and TEM to confirm the standard mesoporous nature. The CHN result shows that the alanine groups have been successfully functionalized on the surface of MCM-41 while the functionalization of alanine groups on MCM-41 were also confirmed by FTIR spectra. The total basic sites of 16Alanine-MCM-41 determined by TPD-CO2 are higher than that of 8Alanine-MCM-41 and enhance to lead the Knoevenagel condensation of furfural and acetylacetone under solvent-free condition. A variety of reaction parameters such as reaction time, temperature, mole ratio and solvents were studied to find an optimum parameter. The Alanine MCM-41 catalysts were successively recovered and reused several times without loss of catalytic activity because of strongly anchored the alanine groups on inner pore of MCM-41, as confirmed by FTIR spectra. Compared to 8Alanine-MCM-41, the 16alanine-MCM-41 gives higher catalytic activity in this reaction because its total base sites lead to produce a major product, 3-(2-furylmethylene)-2,4-pentanedione (FMP) with 100% selectivity using the best parameters like 1:1 M ratio of furfural: acetylacetone, 100 °C and 30 min.